Relationship Between Area and Capacity of Hydrogen Refueling Stations and Derivation of Design Recommendations - Armin Stein; Bastian Nolte; Umut Volkan Kizgin; Ole Grünewald; Güven Yurtseven; Thomas Vietor (Hydrogen)
Hydrogen plays a pivotal role in the decarbonization of the transport sector, necessitating the development of an adequate infrastructure in the form of hydrogen refueling stations (HRSs) to support hydrogen-powered vehicles. This study investigates the characteristics of hydrogen refueling stations to optimize their spatial design and provide key performance indicators for spatial efficiency. An overview of HRS components and their operational requirements is provided, alongside the classification of stations into distinct categories. The primary focus is on analyzing the relationship between station area and capacity. Utilizing spatial data from hydrogen stations, areas are determined through Google Maps analysis. Linear and power regression models are applied to quantify the relationship, with both models proving effective for capturing these dynamics. Based on the findings, spatially efficient design recommendations are proposed, supplemented by examples and a conceptual blueprint for optimized HRS construction, which are then summarized in a morphological design catalog.